Abnormal ETM in the North Passage of the Changjiang River Estuary: Observations in the wet and dry seasons of 2016. (31st October 2019) - Hua, Xia; Huang, Huiming; Wang, Yigang; Lan, Yinyu; Zhao, Kun; Chen, Dake
Abstract: Hydrodynamics and the estuarine turbidity maximum (ETM) were investigated along the Deepwater Navigation Channel (DNC) in the North Passage (NP) of the Changjiang River Estuary (CRE) during spring tides in March (dry season) and July (wet season) in 2016. The along-channel water current, salinity, and suspended sediment concentration (SSC) were measured and compared with a study undertaken in 2012. Results show that the magnitude of SSC in the dry season was significantly larger than that in the wet season in 2016, which was contrary to the results obtained in 2012 and the commonly held understanding that SSC is much higher in wet seasons than dry seasons in this region. Despite the abnormal magnitude of the SSC, the spatial distribution agreed with that of the 2012 observations, and corresponded to the salinity distribution. By analysing the bottom sediment flux and sediment transport over a flood-ebb tidal cycle, the immediate cause of the abnormal SSC magnitudes was found. In the dry season, the resuspension fluxes were more than doubled and tidal pumping terms were significantly larger than of those in the wet season, thus indicating that the resuspension effect was much stronger and able to bring more sediment into the water. Although the strong resuspension effect in the dry season was partly due to a slightly higher tidal dynamic, it was mainly due to the availability of sufficient sediment for resuspension, as induced by the strong cold-air front several days previous. On the contrary, the weak resuspension effect under a similar tidal dynamic in the wet season, was associated with insufficient sediment availability as a result of the limited influence of the typhoon in 2016. In addition, the quantity of sediments available for resuspension influenced the mobile suspension (MS) events of the ETM. Local resuspension and along-channel advection were both important in SSC variation processes and the effect of along-channel advection was more distinct when there was insufficient sediments for resuspension.